Entrepreneurial and business elites of China : the Chinese returnees who have shaped modern China = Hai gui tui dong Zhongguo : Zhongguo dang dai hai gui chuang ye ji shang jie jing ying - Zhang, Wenxian, 1963-; Wang, Huiyao; Alon, Ilan (Emerald, 2011)
"This important reference title focuses exclusively on the elite entrepreneurs of new China and contains 100 substantial profiles of top overseas returnees who have made noteworthy contributions to the Chinese economy since the reform era began in 1978. For the purpose of this book, a returnee is defined as a Chinese native who was born in China, left to study overseas as a student, visiting scholar or guest researcher for over one year, and has returned to China to work on a permanent basis. This edited book begins with an introduction outlining the common characteristics of the returnees, and their impacts on Chinese society in general and economic development in particular. The biographical work summarizes each individuals life and business career, with a central focus on his/her accomplishments and the key roles played in the new Chinese economy. Also included are: references; a chronology of major events in Chinese business development and the new study abroad movement since the economic reform began in 1978; a bibliography of books, articles and related materials; a list of common abbreviations; and English-Chinese cross references of individual and company names indexed in the book." -- Publisher's information.